Symbolic meaning of architecture and ornaments in the 19th century’s Taoist temple among temple committee in the Klang Valley, Malaysia - Yeong, Yin Mei (2021)
Taoist temple is a specific religious and cultural landmark that carries symbolic meaning. The ornaments and architecture buildings serve as a conventional system and perpetual symbols, mainly to pass down to the next generation. Nevertheless, research has demonstrated that the younger generation in Malaysia hardly understood the symbolic meanings of the architecture and ornaments in the Taoist Temples. This research aims to identify the symbolic meaning of the architecture and ornaments, subsequently to assess the Temple Committee’s understanding of the symbolic meaning of the architecture and ornaments of the Taoist temples constructed in the 19th century in Klang Valley, and lastly to recommend a framework of the symbolic meaning of Taoist architecture and ornaments for knowledge dissemination. Site observational study and semistructured interviews with the Temple Committee in ten Taoist Temples revealed the understanding of the temples physical attributes of the architecture and ornaments. In this study, architectural drawings, sketches, photographs of the samples, and voice recordings facilitated the Descriptive Analysis process. The findings show that the evolutionarily constructed architectural attributes of the samples built in the 19th century embraced less Royal symbolic meaning for the upper section. Nevertheless, it was discovered that the roof of the foyer carries a royal symbolic meaning and the upper section of the main hall depicted the Malay vernacular architecture features such the ventilated roof, which is signifying a Sino-Malay character, reflecting the man-made production during the 19th century, which was dedicated to the Chinese diaspora. Additionally, most of the ornaments discovered applied in the figural form to express the folklore tales in the theory of Theism. This study also reveals that the respondents were able to describe the simple keywords of the symbolic meaning, in religious approach and clueless for the royal symbolic meaning. Furthermore, they could not comprehensively explain the symbolic meaning of the architecture and ornaments due to the limitation of knowledge. Therefore, the recommended framework for knowledge dissemination is to synthesize the power of relevant stakeholders with joint efforts in a multidisciplinary capacity in order to promulgate the Chinese legacy to the future generation.